Neonatal Bacille Calmette-Guérin vaccination and tuberculin skin test reactions at 2- and 6-months: Effects on mortality up to 1 year of age. Issue 50 (8th December 2021) - Schaltz-Buchholzer, Frederik; Roth, Adam; de Bree, L. Charlotte J.; Biering-Sørensen, Sofie; Timmermann, Clara Amalie Gade; Monteiro, Ivan; Aaby, Peter; Benn, Christine Stabell
Highlights: Adequate vaccination with certain BCG strains induces positive tuberculin skin tests In 6 cohorts (n>12000), tuberculin reactions reduced infant mortality with 40% Improving coverage & the administration of certain BCG strains might reduce mortality Abstract: Background: In randomized trials, Bacille Calmette-Guérin (BCG) vaccine has been associated with reduced all-cause mortality. BCG-induced Tuberculin Skin Test (TST) reactions have also been associated with reduced all-cause mortality. We aimed to assess the association between TST responses and subsequent mortality in three birth cohorts and conducted a meta-analysis of existing studies. Methods: Observational study within three Guinea-Bissau BCG trial birth cohorts (conducted 2002–04, 2009–2013 and 2014–18) that encompassed children who were BCG-vaccinated within 28 days with TSTs performed at 2- (n = 1389) and 6-months (n = 2635) of age. We evaluated TST reaction determinants by binomial regression and assessed the association between TSTs > 1 mm (reactors) vs. ≤ 1 mm (non-reactors) and subsequent mortality risk up to age 12 months in Cox-models providing Mortality Rate Ratios (MRRs). We searched PubMed for studies to calculate meta-estimates of the association between TST reactivity by age 2- and 6-months and all-cause mortality. Results: Large post-vaccination wheal size was associated with 6-month TST positivity and so was receiving BCG-Denmark or BCG-Japan, compared with BCG-Russia. By age 2 months, 22% (302/1389) of infants were TST reactors with a 2–12-month mortality risk of 1.7% (5/302) vs. 3.3% (36/1087) for non-reactors, the corresponding reactor/non-reactor MRR = 0.49 (0.19–1.26). By age 6 months, 44% (1149/2635) of infants were reactors and the 6–12-month mortality risk was 0.4% (4/1149) vs. 0.6% (9/1486) for non-reactors, the MRR = 0.87 (0.27–2.86). The literature search provided 3 studies. The meta-analysis revealed a uniform pattern of reduced mortality associated with TST reactivity, a TST response by 2 months being associated with an MRR of 0.59 (0.39–0.90); for 6-month TST responses the MRR was 0.65 (0.43–1.00). Conclusion: Among BCG-vaccinated infants, TST reactions were associated with markedly reduced mortality. Improved vaccination technique and using certain BCG strains could lead to a higher TST reaction prevalence, which would enhance BCG's beneficial non-specific effects.